Pengaruh Pembelajaran pada Mata Pelajaran Pendidikan Agama Islam terhadap Kecerdasan Spiritual Peserta Didik di Kelas XI SMA IT Al-Madinah - Yuliyanti, Yuliyanti; Kasman, Rusdi; Husni, Rahmatul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Low spiritual quotient is increasingly observed among teenagers, including at SMA IT Al-Madinah. Even though the school has a sufficient curriculum and facilities, however, the quality of learning of Islamic religious education subject is crucial for enhacing students’ spiritual quotient. This study aims to assess the quality of learning, the level of spiritual quotient and the influence learning of Islamic religious education subjects on students' spiritual quotient in class XI at SMA IT Al-Madinah. The research employs a quantitative survey method with data collection through questionnaires. Data analysis includes validity and reliability tests, followed by normality and homogeneity tests, and finally hypothesis testing using simple linear regression. The results indicate that: (1) The quality of Islamic religious education subject learning is categorized as fairly good, with an interval range of 62.442 ≤ Xi < 73.158, meaning 50 out of 71 respondents, or 70.4%, rated it positively. (2) The level of students' spiritual quotient in class XI falls within an interval range of 56.920 ≤ Xi < 67.160, indicating that 52 out of 71 respondents, or 73.2%, are in the moderate category. (3) Simple linear regression testing shows a significant value of 0.000 < 0.05 with an R Square value of 0.332, indicating that The Influence of Learning of Islamic Religious Education Subject on The Spiritual Quotient of Grade XI Students at SMA IT Al-Madinah by 33,2%.